Dynamic characteristics of priority control system for high-speed on–off digital valve. (21st April 2015) - Zeng, Yishan; Wang, Daoming; Zi, Bin; Zeng, Qi
Dynamic characteristics of the priority control system are of great influence to the control effect, response speed, and working stability of the high-speed on–off digital valve. The main focus of this study is on revealing the dynamic properties of the priority control system for a developed high-speed on–off digital valve. In this article, a detailed introduction to the high-speed on–off digital valve and its priority control system is performed first, which includes the system function, structural composition, and operation principle. Thereafter, a simulation model of the priority control system is established using the AMESim software and the dynamic characteristics are simulated. Simulation results including the variations in the pulse-width modulation signal, coil current, and the main spool displacement of the directional valve are presented and discussed. They indicate that the opening time of the main spool increases with the duty ratio of the voltage signal. Moreover, the main spool displacement is basically equal in one single pulse-width modulation signal cycle, and thus, it is proportional to the cycle number of the pulse-width modulation signal. As a consequence, the priority control system possesses a good dynamic characteristic for the high-speed on–off digital valve as a pilot valve to achieve proportional control of main spool displacement for the directional valve.